Criminal System against Criminal Actions Health Quarantine Violations - Slamet Pribadi (Budapest International Research and Critics University, 2022)
Corona Virus Disease 2019 (Covid-19) is an infectious disease outbreak that has the potential to cause a public health emergency. The laws and regulations promulgated by the government are intended to provide a new direction for the Indonesian state in responding to any disease outbreaks that can occur at any time, especially in responding to the current Covid-19 pandemic. Quarantine is the restriction of a person or even a group of people in an area in an area where the area has been infected with an outbreak of an infectious disease. The presence of quarantine can prevent the spread of the Covid-19 outbreak and minimize the transmission of Covid-19. The purpose of this study is to find out how the implementation of the criminal system in providing punishment for perpetrators of health quarantine violators is and what problems are encountered in implementing health quarantine in overcoming Covid-19. The research method used is normative law research with a statute approach. And by collecting data in the form of primary legal materials, secondary legal materials, and tertiary legal materials. The results of this study indicate that cases of criminal acts of health quarantine violators are still prevalent, due to lack of attention to punishment for perpetrators of health quarantine violators. It is also necessary to increase the role of the government and the community in tackling the spread of the Covid-19 outbreak.